Health principles as one of the major factors affecting the development of organic agriculture in Ukraine - Mylovanov, Yevhen (Herald of Economics, 2019)
Taking into account some of the important parameters of human health, the study presents a comparative analysis of organic and  conventional  agricultural  production, and highlights how organic management practices affect balanced food systems. It is pointed out that consumption of organic food can reduce the risk of developing allergies, overweight and obesity. Even though organic food products are much healthier to eat, there is still a need to provide more evidence why organic food is more beneficial. The author considers research experiments on animals and concludes that animal feed from organic and conventional agricultural production influences animals differently. It is noted that in organic agricultural production the use of synthetic pesticides is prohibited, whereas in conventional agricultural production pesticide residues in fruit and vegetables are the main source of chemicals affecting human health. The study reviews changes in the use of plant protection products by domestic farms and compares the intensity of pesticide consumption in Ukraine and other countries of the world in recent years. According to epidemiological studies, pesticides have an adverse effect on cognitive development of children and carcinogenic risks to public health. However,  this data has not been used   in official risk assessments for individual pesticides. It is also stressed that promoting organic agricultural production reduces the professional impact of pesticides on agricultural workers and rural residents. Particular attention is drawn to the issue of using antibiotics in conventional animal farming, which is considered to be one of the major factors explaining why people have developed resistance to antibiotics, as opposed to organic animal farming, where the use of antibiotics is very limited. The author claims that organic agricultural production has a number of documented and potential advantages for human health, and is therefore more likely to improve health outcomes. Based on the findings that production and consumption of organic food has a potential positive effect on people’s health, a number of recommendations are made concerning guidelines for further research that will contribute to promoting and maintaining human health, animal health, protecting the earth and environment.